2011
DOI: 10.1152/ajpregu.00234.2011
|View full text |Cite
|
Sign up to set email alerts
|

Low-magnitude whole body vibration with resistive exercise as a countermeasure against cardiovascular deconditioning after 60 days of head-down bed rest

Abstract: YH. Low-magnitude whole body vibration with resistive exercise as a countermeasure against cardiovascular deconditioning after 60 days of head-down bed rest. Am J Physiol Regul Integr Comp Physiol 301: R1748 -R1754, 2011. First published September 7, 2011 doi:10.1152/ajpregu.00234.2011.-Whole body vibration with resistive exercise is a promising countermeasure against some weightlessness-induced dysfunctions. Our objective was to study whether the combination of low-magnitude whole body vibration with a resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…In a recent meta-analysis of relevant studies, Games et al (2015) also suggested that exposure to WBV of lower frequencies resulted in a greater response in peripheral BF than did higher frequencies. It has been postulated that exposure to WBV causes activation of muscle spindle receptors with subsequent generation of vibration tonic reflexes causing an increase in muscle metabolic demand and oxygen consumption (Cardinale & Wakeling, 2005;Coup e et al, 2011;Kasai et al, 1992;Kerschan-Schindl et al, 2001;Rothmuller & Cafarelli, 1995). This causes rhythmic contraction and relaxation of the precapillary sphincter with subsequent vasodilation Hazell et al, 2008).…”
Section: Author/s and Reference Year Limitationsmentioning
confidence: 99%
“…In a recent meta-analysis of relevant studies, Games et al (2015) also suggested that exposure to WBV of lower frequencies resulted in a greater response in peripheral BF than did higher frequencies. It has been postulated that exposure to WBV causes activation of muscle spindle receptors with subsequent generation of vibration tonic reflexes causing an increase in muscle metabolic demand and oxygen consumption (Cardinale & Wakeling, 2005;Coup e et al, 2011;Kasai et al, 1992;Kerschan-Schindl et al, 2001;Rothmuller & Cafarelli, 1995). This causes rhythmic contraction and relaxation of the precapillary sphincter with subsequent vasodilation Hazell et al, 2008).…”
Section: Author/s and Reference Year Limitationsmentioning
confidence: 99%
“…In case of orthostatic intolerance, the 5 minutes prior to intolerance were chosen for analysis [10]. For the single subject who developed orthostatic intolerance at the third minute of tilt, the 2 min mark prior to intolerance was analyzed.…”
Section: Tilt Testmentioning
confidence: 99%
“…Analysis of orthostatic responses, power spectrum analysis of heart rate variability, and analysis of the spontaneous baroreflex sensitivity was performed as previously described [10]. Skin vascular resistance (SVR) was calculated by dividing mean blood pressure by skin blood flow.…”
Section: Tilt Testmentioning
confidence: 99%
“…() but with fewer sets per exercise. In another 8‐week intervention, WBVET prevented the increase in resting sympathovagal balance (LF/HF) induced by 60 days of head‐down bed rest in young men (Coupe et al ., ). This was attributed to an improved arterial baroreceptor function with WBVET, which consisted of daily exposure to five 4‐min stretches with vibration followed by 1 min rest, for a total daily duration of 24 min.…”
Section: Effects Of Wbvet On Resting Hrvmentioning
confidence: 97%
“…The potential mechanisms underlying the effect of WBVET on HRV may include an increase in baroreflex sensitivity (Collier et al ., ; Kouidi et al ., ). Certainly, evidence suggests that WBVET limits the decrease in the spontaneous baroreflex sensitivity induced by prolonged head‐down bed rest in young healthy men (Coupe et al ., ). Another potential mechanism could be an increase in nitric oxide (NO) levels.…”
Section: Potential Mechanisms For the Improvement In Hrv By Wbvetmentioning
confidence: 97%